2019
DOI: 10.1002/chem.201902353
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on the Photogeneration of Hydrogen by Decamethylruthenocene

Abstract: Detailed studies on hydrogen evolution by decamethylruthenocene ([Cp* 2 Ru II ]) highlighted that metallocenes are capable of photoreducing hydrogen without the need for an additionals ensitizer.E lectrochemical, gas chromatographic, and spectroscopic (UV/Vis, 1 Ha nd 13 CNMR) measurements corroborated by DFTc alculations indicated that the production of hydrogen occurs by at wo-stepp rocess. First, decamethylruthenocene hydride [Cp* 2 Ru IV (H)] + is formed in the presence of an organic acid. Subsequently, [C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 86 publications
(211 reference statements)
0
15
0
Order By: Relevance
“…Hydrogen generation is the easy part of the scheme, as for example metallocenes, such as decamethylferrocene, dissolved in the organic phase can even reduce aqueous protons in the dark at the interface. To reach higher potentials and to fully exploit the light energy, we have recently [20][21] shown that we could use molecules such as decamethylruthenocene, which have a dark redox potential of 0.75V in dichloroethane versus an aqueous standard hydrogen electrode as shown below. The bottleneck for designing an efficient batch water splitting process is oxygen evolution, but a recent work of Ragstar et al 22) using BiVO4 at the water-butyronitrile interface is very promising as it was shown that oxygen could be photoproduced at the interface using the lipophilic [Co(bpy)3] 3+ ion as a redox mediator and where the adjacent aqueous phase acts as a proton pump.…”
Section: Batch Water Splittingmentioning
confidence: 99%
“…Hydrogen generation is the easy part of the scheme, as for example metallocenes, such as decamethylferrocene, dissolved in the organic phase can even reduce aqueous protons in the dark at the interface. To reach higher potentials and to fully exploit the light energy, we have recently [20][21] shown that we could use molecules such as decamethylruthenocene, which have a dark redox potential of 0.75V in dichloroethane versus an aqueous standard hydrogen electrode as shown below. The bottleneck for designing an efficient batch water splitting process is oxygen evolution, but a recent work of Ragstar et al 22) using BiVO4 at the water-butyronitrile interface is very promising as it was shown that oxygen could be photoproduced at the interface using the lipophilic [Co(bpy)3] 3+ ion as a redox mediator and where the adjacent aqueous phase acts as a proton pump.…”
Section: Batch Water Splittingmentioning
confidence: 99%
“…Additional single-component photoelectrocatalysts for H 2 evolution based on Ru and Rh have appeared recently, but like the Ir systems these also rely on precious metals (Figure ). It is likely that any practical system for solar fuels generation will require the light harvester to be composed of abundant and affordable elements, but to date, there have been no reports of molecular photoelectrocatalysts based on first-row transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Illustrated inFigure 4Ais a conceptual membraneless biphasic approach to photo-driven water splitting. This approach overcomes problems encountered at solid electrode/liquid interfaces, such as corrosion[39,40]. Two separate biphasic compartments are designed, one carrying out the photo-driven WOR in the presence of a recyclable electron acceptor "A" in the organic phase and the other carrying out the photo-driven HER with a reversible electron donor (D) in the organic phase.…”
mentioning
confidence: 99%
“…A is a recyclable electron acceptor that is photo-reduced to oxidise water in the anodic compartment, and D is a recyclable electron donor photo-oxidised to reduce protons in the cathodic compartment. This figure has been reproduced with permission from ref [39]…”
mentioning
confidence: 99%